Digitizing, Organizing and Managing an Audio-Visual Archive: The Trevor Jones Archive at the University of Leeds - Cooper, David; Sapiro, Ian; Anderson, Laura; Hall, Sarah (Journal of Film Music, 2016)
Between 2005 and 2013, film-music composer Trevor Jones donated around 1000 items relating to his film and television scores to the University of Leeds. The collection includes audio and video materials alongside associated paperwork, and some musical sketches and scores. In order to undertake research into the Trevor Jones Archive, the entire collection required digitization and cataloguing, both to facilitate navigation of the materials, and enable understanding of the relationships between them and the processes that they document. This paper considers the practicalities of working with the archive including matters relating to the digitization of a range of analogue and paper-based items, the creation of appropriate metadata and repository structures, and the prioritization of some parts of the collection over others. It is hoped that the lessons learned through this activity highlight some of the issues and considerations of working with archival audio-visual materials, and provide a roadmap for those working with similar collections.